The neuroanatomy of the siboglinid Riftia pachyptila highlights sedentarian annelid nervous system evolution - Rimskaya-Korsakova, Nadezhda N. (PLoS One, 2018)
Tracing the evolution of the siboglinid group, peculiar group of marine gutless annelids, requires the detailed study of the fragmentarily explored central nervous system of vestimentiferans and other siboglinids. 3D reconstructions of the neuroanatomy of Riftia revealed that the “brain” of adult vestimentiferans is a fusion product of the supraesophageal and subesophageal ganglia. The supraesophageal ganglion-like area contains the following neural structures that are homologous to the annelid elements: the peripheral perikarya of the brain lobes, two main transverse commissures, mushroom-like structures, commissural cell cluster, and the circumesophageal connectives with two roots which give rise to the palp neurites. Three pairs of giant perikarya are located in the supraesophageal ganglion, giving rise to the paired giant axons. The circumesophageal connectives run to the VNC. The subesophageal ganglion-like area contains a tripartite ventral aggregation of perikarya (= the postoral ganglion of the VNC) interconnected by the subenteral commissure. The paired VNC is intraepidermal, not ganglionated over most of its length, associated with the ciliary field, and comprises the giant axons. The pairs of VNC and the giant axons fuse posteriorly. Within siboglinids, the vestimentiferans are distinguished by a large and considerably differentiated brain. This reflects the derived development of the tentacle crown. The tentacles of vestimentiferans are homologous to the annelid palps based on their innervation from the dorsal and ventral roots of the circumesophageal connectives. Neuroanatomy of the vestimentiferan brains is close to the brains of Cirratuliiformia and Spionida/Sabellida, which have several transverse commissures, specific position of the giant somata (if any), and palp nerve roots (if any). The palps and palp neurite roots originally developed in all main annelid clades (basally branching, errantian and sedentarian annelids), show the greatest diversity in their number in sedentarian species. Over the course of evolution of Sedentaria, the number of palps and their nerve roots either dramatically increased (as in vestimentiferan siboglinids) or were lost.